PENGARUH KEDISIPLINAN SISWA TERHADAP PRESTASI BELAJAR SISWA KELAS IV SD MENGGUNAKAN METODE ANGKET DENGAN TEKNIK CLUSTER SAMPLING - Ika Susanti; Ninik Dwi Atmini (LPPM Universitas Sains dan Teknologi Komputer, 2022)
This study aims to describe and analyze the effect of student discipline on learning achievement in fourth grade students of SD N Batursari 01 Mranggen in the 2021/2022 Academic Year. This type of research is descriptive statistics. The population in this study were all fourth grade elementary school students, totaling 200 students. The research sample was selected by cluster sampling technique. The research data was collected using a questionnaire method given to 117 students from SD N Batursari 03 Mranggen, SD N Batursari 02 Mranggen, and SD N 01 Mranggen. The data obtained were tested using a simple regression test with the help of the SPSS for Windows version 16.0 . program The results of this study indicate that student discipline is classified as very high with an average of 79.38. The test results show that the student discipline variable has a significant effect on the student achievement variable, with the results of the calculation tcount = 2,513 meaning tcount > ttable (ttable = 1.9808). Thus, one of the reasons for the high and low learning achievement of students is the discipline of students by 52%, but it is also caused by other factors of 48%, both internal and external factors.